2014
DOI: 10.5194/acp-14-7213-2014
|View full text |Cite
|
Sign up to set email alerts
|

Radiative signature of absorbing aerosol over the eastern Mediterranean basin

Abstract: The effects of absorbing aerosols on the atmospheric radiation budget and dynamics over the eastern Mediterranean region are studied using satellites and ground-based observations, and radiative transfer model calculations, under summer conditions. Climatology of aerosol optical depth (AOD), single scattering albedo (SSA) and size parameters were analyzed using multiyear (1999-2012) observations from Moderate Resolution Imaging Spectroradiometer (MODIS), Multi-angle Imaging SpectroRadiometer (MISR) and AErosol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 87 publications
5
35
0
Order By: Relevance
“…3), which is expected due to the different geographical areas and periods of interest between the two studies. The smooth reduction with increasing wavelength in the SSA of pure soot in this study, as well as the abrupt decrease from 1 to 3 µm in the water-soluble aerosol modes, is consistent with the findings of Mishra et al (2014Mishra et al ( , 2015 for the polluted air masses over the Mediterranean as well as with the respective model values used in the study by Takemura et al (2002) for carbonaceous and sulfate aerosol.…”
Section: The Aerosol Optical Propertiessupporting
confidence: 77%
“…3), which is expected due to the different geographical areas and periods of interest between the two studies. The smooth reduction with increasing wavelength in the SSA of pure soot in this study, as well as the abrupt decrease from 1 to 3 µm in the water-soluble aerosol modes, is consistent with the findings of Mishra et al (2014Mishra et al ( , 2015 for the polluted air masses over the Mediterranean as well as with the respective model values used in the study by Takemura et al (2002) for carbonaceous and sulfate aerosol.…”
Section: The Aerosol Optical Propertiessupporting
confidence: 77%
“…Smirnov et al (1995) found that for clean oceanic conditions, AOD was below 0.1 (at 550 nm) and Pace et al (2006) found an average value of 0.11 for the same marine conditions. In the Mediterranean sea in particular, Fotiadi et al (2006) reported a value of 0.15 in Crete in the background corresponding to marine aerosols and Mishra et al (2014) found a mean AOD over the eastern Mediterranean for marine aerosols (June-August 2010) of 0.06 ± 0.01. Furthermore, it should be noted that AOD is not very sensitive to the wavelengths during these 5 days due to the presence of coarse particles.…”
Section: Pma Physical Properties In Comparison With Dust and Bbp Periodsmentioning
confidence: 99%
“…Only night-time aerosol backscatter at 532 nm is used in this study to avoid possible noise in day-time data. All night-time aerosol backscatter profiles are screened for the artifacts using the methodology provided by Mishra et al (2014). More details about the CALIPSO algorithm and it's description are described by Winker et al (2006) and Labonne et al (2007).…”
Section: Cloud-aerosol Lidar and Infrared Pathfinder Satellite Observmentioning
confidence: 99%